What do students and engineers have to say about communicative competence in technical oral presentations? - Bhattacharyya, E. (Universiti Putra Malaysia, 2015)
This article reports how the notion of communicative competence was perceived by engineering students and engineers during 16 final year technical oral presentation sessions. Six sub-sets associated to linguistic and rhetorical competence such as brevity and terminology; confident, interactive and argumentative language; visual language; humour; formality, and exchange of questions are deemed necessary. There is, however, notable diversity in the participants' perception of the said notion. Engineers stressed contextualised real-world application presentation, while students were drawn toward academically inclined structured content based type of presentation. Implications of the study for English Language teaching in the ESL context are discussed. Â© Universiti Putra Malaysia Press.